Editorial - Manninezhath , Thomas (Journal of Dharma, 1995)
The term Yoga can be viewed from various perspectives, It shall be studied asa system of philosophy, popular, non-systematic yoga and non-brahmanic yoga. It can also refer to any ascetic technique and’ any method of meditation. In all its understanding, yoga implies two things: a preliminary detachment from matter and an emancipation from the binding forces of human existence. This number of the Journal of Dharma focuses on one of the essential aspects of Yoga, l.e, Yoga and Search for Holiness. Yoga is the corpus of means for holiness. Abstentions and observances (yama and niyama), postures and rhythm of respiration (iisana and’ prafJayama), withdrawal of the senses’and fixed attention (pratyahiira and dhiirana), contemplation and concentration (dhyiina and samadhi) are the ways for exterminating suffering, the means of realizing the Being and the techniques for attaining liberation.